Solving a Split Feasibility Problem by the Strong Convergence of Two Projection Algorithms in Hilbert Spaces. (17th March 2021) - Hammad, Hasanen A.; Rehman, Habib ur; Gaba, Yaé Ulrich
Abstract : The goal of this manuscript is to establish strong convergence theorems for inertial shrinking projection and CQ algorithms to solve a split convex feasibility problem in real Hilbert spaces. Finally, numerical examples were obtained to discuss the performance and effectiveness of our algorithms and compare the proposed algorithms with the previous shrinking projection, hybrid projection, and inertial forward-backward methods.